2001
DOI: 10.1046/j.1445-6664.2001.00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of physiological effects of fluazifop‐butyl and sethoxydim on oat (Avena sativa L.)

Abstract: Laboratory experiments were conducted to compare the physiological effects of two herbicides: fluazifop‐butyl {butyl (RS)‐2‐[4‐(5‐trifluoromethyl‐2‐pyridyloxy)phenoxy]‐propionate} and sethoxydim {(±)‐2‐[1‐(ethoxyimino)butyl]‐5‐[2‐(ethylthio)propyl]‐3‐hydroxy‐2‐cyclohexen‐1‐one} on oat (Avena sativa L. cv. Zenshin). The herbicides strongly inhibited growth of oat and induced chlorosis at the basal part of shoots and ethylene production from the seedlings. The phytotoxicity of these herbicides in oat seedlings w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In a previous paper, we reported that the first visible symptom in AOPP or CHD‐treated grass was chlorosis appearing at the basal part of shoots (Luo et al . 2001).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous paper, we reported that the first visible symptom in AOPP or CHD‐treated grass was chlorosis appearing at the basal part of shoots (Luo et al . 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, fluazifop‐butyl induced wilting and necrosis of A. hispidum leaves within 20 HAT. In addition, the period required to induce seedling death was distinctly different; approximately 15 days were necessary for oat (Luo et al . 2001), while only 48–72 h for A. hispidum (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations